Die Bedeutung des Treforest Industrial Estate für das Bergbaurevier im Hinterland von Cardiff - Dahlke, Jürgen (ERDKUNDE, 1967)
When, twenty years after the last World War, one weighs up the development of the Taff coalfield, it is clear that the severe inter-war crisis has been overcome. Although the newly-settled factories do not wholly belong to the fastest expanding groups, they provide a viable economic base which gives cause for reasonable optimism. Unemployment has been sharply reduced and a new body of skilled workers created. In addition, mining is experiencing a certain upturn in activity. Hand in hand with the economic renewal of the area has gone a spatial restructuring. The location of the Estate has given the Taff Vale below Pontypridd an important role in the economic life of the region, a role which lifts it above the level of the other mining valleys. Although this part of the Taff Vale lies within the geo logical confines of the coalfield, its special status makes it rather part of the economic area of the Vale of Glamorgan to the south, in which newly-introduced finished-goods industries have found their optimum location in eastern South Wales, near existing heavy industry. The Treforest Industrial Estate clearly demonstrates the polarity between the young, dynamic industrial area on the coast and the old coalfield area to the north, now largely robbed of its raison d'etre.